JUS MENTIMUN DAPAT MENURUNKAN TEKANAN DARAH PADA WANITA MENOPAUSE - Fika Kusmawati; Sri Dinengsih; Risza Choirunisa Choirunisa (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: The prevalence of hypertension in Indonesia is 45.9% for 55-64 years old, 57.6% for 65-74 years old and 63.8% for >75 years old. It is estimated that people with hypertension in Indonesia reach 15 million people but only 4% are controlled hypertension. The prevalence is 6-15% in the elderly, 50% are not aware of being hypertensive patients, so they tend to become severe hypertension because they do not avoid and do not know the risk factors and 90% are essential hypertension.The Purpose Knowing the effect of giving cucumber juice on blood pressure in postmenopausal women in the work area of the Puskesmas baktijaya, south tangerang city in 2021 in the intervention group and control group.Methodology: The researcher used a quasi-experimental research design with a pre-test and with control design. The sample in this study amounted to 36 people consisting of 18 intervention groups and 18 control groups. The sampling technique used was purposive sampling. The research instrument consisted of an observation sheet on the state of blood pressure in patients with hypertension before being given cucumber juice and changes in blood pressure in postmenopausal women with hypertension after being given cucumber juice.Research result: There was an effect of giving cucumber juice on decreasing blood pressure in the intervention group with a mean rank of 13.72 and in the control group with a mean rank of 23.28. With a p value of 0.005 < 0.05. There is an effect of giving cucumber juice to decrease diastolic blood pressure in the intervention group with a mean rank of 23.94 and in the control group with a mean rank of 13.06. With a p value of 0.001 <0.05.Conclusions and suggestions: Giving cucumber juice can affect the reduction of blood pressure in postmenopausal women. Suggestion giving cucumber juice to menopausal women or the public can be applied and consumed regularly. Keywords:Menopausal Women, Hypertension, Cucumber ABSTRAK Latar Belakang: Prevalensi hipertensi di Indonesia sebesar 45,9% untuk umur 55-64 tahun, 57,6% umur 65-74 tahun dan 63,8% umur >75 tahun. Diperkirakan penderita hipertensi di Indonesia mencapai 15 juta jiwa tetapi hanya 4% yang merupakan hipertensi terkontrol. Prevalensi 6-15% pada orang lanjut usia, 50% tidak menyadari sebagai penderita hipertensi sehingga mereka cenderung menjadi hipertensi berat karena tidak menghindari dan tidak mengetahui faktor risikonya dan 90% merupakan hipertensi esensial.Tujuan: Mengetahui pengaruh pemberian jus mentimun terhadap tekanan darah pada wanita menopause di wilayah kerja puskesmas baktijaya kota tangerang selatan tahun 2021 pada kelompok intervensi dan kelompok kontrol.Metodologi: Peneliti menggunakan desain penelitian quasi-eksperimen dengan rancangan pre-test and with control. Sampel dalam penelitian berjumlah 36 orang yang terdiri dari 18 kelompok intervensi dan 18 kelompok kontrol. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen penelitian terdiri dari pada lembar observasi keadaan tekanan darah pada penderita hipertensi sebelum diberikan jus mentimun dan perubahan tekanan darah pada wanita menopause yang mengalami hipertensi setelah diberikan jus mentimun.Hasil Penelitian: Ada pengaruh pemberian jus mentimun terhadap penurunan tekanan darah pada kelompok intervensi dengan mean rank 13,72 dan pada kelompok kontrol dengan mean rank 23,28. Dengan nilai p value sebesar 0,005 < 0,05. Ada pengaruh pemberian jus mentimun terhadap penurunan tekanan darah diastolik pada kelompok intervensi dengan mean rank 23,94 dan pada kelompok kontrol dengan mean rank 13,06. nilai p value sebesar 0,001 < 0,05.Simpulan Pemberian jus mentimun dapat berpengaruh terhadap penurunan tekanan darah pada wanita menopause.Saran pemberian jus mentimun pada wanita menopause atau masyarakat dapat diterapkan dan dikonsumsi secara rutin. Kata Kunci : Wanita Menopause, Hipertensi, Mentimun